A Computational System Approach To Develop Students’ Emotion Oriented System as Feedback Tool for Lecturers to Enhance Teaching and Learning - Deshinta, Arrova Dewi; Zaidatol Haslinda, Abdullah Sani; Jeremiah, Premylla (Convergence Information Society(CIS), 2012)
The quality of learning depends on aspects that integrate positive environment in the classroom. Previous works have shown that positive environment do create positive emotion and positive emotion do affect positive learning behavior. When students experience positive emotion, the learning process can be enhanced and when students experience negative emotion, learning process can be disabled. Therefore managing students learning in the classroom means managing emotions. This paper presents the efforts in recognizing student’s emotion to promote interactive teaching learning atmosphere in a Higher Education environment that is served as an alternative feedback tool for lecturer to enhance students learning experiences. This system suggests lecturers to identify whether their teaching style has positive impact on students learning behavior by recognizing student’s emotion in the classroom. This system proposes the composition of positive class emotion as result of positive student’s emotion to encourage lecturers to retain their teaching style or to improve it. In this paper we explore the possibilities of capturing emotions by various techniques. We compare some of the existing works and identify how emotions can be modeled in order to enhance its services and response and able to suggest meaningful information to users. We also define and discuss the appropriate capacity of meaningful information to generate analysis and recommendations according to theory of teaching and learning. We do our experiments in INTI International University, Nilai Malaysia observing approximately 200 students from various faculties.